Data Driven Educational Planning Strategy: Examining Challenges and Opportunities in the Digital Era - Indah Inayatur Rohmah; Ainur Rofiq; Muhammad Bisri Ihwan (SAINTIS Publishing, 2025)
This study aims to examine and comprehend the implementation of a data-driven approach in educational strategic planning by identifying the challenges encountered and the opportunities that can be leveraged in the digital era. Educational institutions often struggle to maximize the use of data due to infrastructure limitations, low digital literacy, and minimal integration of technology in decision-making processes. This research employs a Research and Development (RD) methodology to design a data-driven implementation model for educational planning. Data collection was conducted through in-depth interviews with various stakeholders, observations of daily data utilization practices, and document analysis of education policies and evaluation reports. The data analysis process utilized triangulation techniques to ensure accuracy and consistency in research findings. The results indicate that a data-driven approach enhances efficiency and precision in educational strategic planning; however, its implementation remains hindered by constraints such as limited human resources, technological infrastructure, and supporting policies. This study recommends capacity building for educators, investment in digital infrastructure, and the development of regulations to safeguard and optimize data utilization. While data-driven approaches hold significant potential to transform educational strategic planning, successful implementation requires comprehensive and well-integrated support.